FRUIT FLIES (DIPTERA: TEPHRITIDAE) AND THEIR PARASITOIDS IN IRRIGATED COFFEE PLANTATIONS IN THE NORTH OF MINAS GERAIS. - CAMARGOS, MARIA GISELY; ALVARENGA, CLARICE DINIZ; GIUSTOLIN, TERESINHA AUGUSTA; OLIVEIRA, PATRÍCIA CRISTINA DO CARMO; RABELO, MARCELO MENDES (Coffee Science - ISSN 1984-3909, 2015)
The objective of this study was to identify the species of fruit flies associated with coffee plants, as well as the seasonal occurrence of the most frequent species and infestation rates in the semiarid region, north of Minas Gerais. The survey was conducted from April 2009 to April 2010 in two coffee plantations of 0.5 ha each one, irrigated and grown under full sun with Red Catuaí cultivar, located in Jaíba, MG. Weekly, there were collections of ripe fruit and for a survey of adult flies were used McPhail traps containing as food bait hydrolyzed protein to 5%. Were obtained 106.233 individuals collected in McPhail traps. From this total, 106,031 belong to Ceratitis capitata (Wied.) and 202 to Anastrepha Schiner: A. dissimilis Stone, A. fraterculus (Wied.), A. manihoti Lima, A. obliqua (Macq.), A. pickeli Lima, A. zenildae Zucchi, A. hadropickeli Canal, Uramoto & Zucchi and A. entodonta Canal, Uramoto & Zucchi.. In fruits were obtained 783 specimens, 779 of these belong to C. capitata and four Anastrepha males no identified. MAD (fly/trap/day) indices rates up to 83 in Area 1 and 132 MAD in Area 2 in the months with higher fruit availability. The highest population peak occurred at the end of the period of fruit maturation (April to June), decreasing after harvesting them. The mean infestation rates ranged 0.005 to 0.415 puparia/fruit and 8 to 366.76 puparia/kg of coffee fruit. The coffee plantations investigated showed high level of infestation of fruit flies and high indices MAD. It was found the presence of the parasitoid Doryctobracon areolatus (Szépligeti) in collected fruits, low rate of natural parasitism occurred.